2007
DOI: 10.1002/jcb.21449
|View full text |Cite
|
Sign up to set email alerts
|

Antisense glutaminase inhibition modifies the O‐GlcNAc pattern and flux through the hexosamine pathway in breast cancer cells

Abstract: Glutamine behaves as a key nutrient for tumors and rapidly dividing cells. Glutaminase is the main glutamine-utilizing enzyme in these cells, and its activity correlates with glutamine consumption and growth rate. We have carried out the antisense L-type glutaminase inhibition in human MCF7 breast cancer cells, in order to study its effect on the hexosamine pathway and the pattern of protein O-glycosylation. The antisense mRNA glutaminase expressing cells, named ORF19, presented a 50% lower proliferation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…The majority of studies focusing on the role of O-GlcNAc in regulating cellular function have been in the context of chronic diseases including cancer, age-related diseases, diabetes, and diabetic complications (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, in 2004 Zachara et al (15) demonstrated for the first time that there was an acute increase in cellular O-GlcNAc levels in response to a range of stress stimuli and importantly that inhibition of this response increased cell death and conversely that augmenting this response increased tolerance of cells to stress.…”
mentioning
confidence: 99%
“…The majority of studies focusing on the role of O-GlcNAc in regulating cellular function have been in the context of chronic diseases including cancer, age-related diseases, diabetes, and diabetic complications (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, in 2004 Zachara et al (15) demonstrated for the first time that there was an acute increase in cellular O-GlcNAc levels in response to a range of stress stimuli and importantly that inhibition of this response increased cell death and conversely that augmenting this response increased tolerance of cells to stress.…”
mentioning
confidence: 99%
“…Although studies have revealed that CA-125 is not tumor specific, 20,21 the strategy of combining multiple tumor markers found in serum has been shown to facilitate the detection of early stage tumors and accurately identify tumor recurrence. 22,23 Unfortunately, serum markers cannot be used to determine tumor volume or location, which is critical information in the clinical management of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oncogenes such as MYC, NF-kB, AKT, tyrosine kinases and tumour suppressor genes including TP53 and PTEN that have been linked to increased glycolysis, have also been implicated in the upregulation of glutamine [28]. Glutamine function as a source of both nitrogen and carbon and contains amino and amido nitrogens, which are transferred to metabolic intermediates in the synthesis of nucleic acids, proteins, and hexosamines making it a crucial nutrient during cell proliferation [29,30]. It is not surprising that novel imaging strategies focusing on glutamine that could provide a valuable complement to 18 F-FDG PET, because glutamine complements glucose in the metabolic platforms that support tumour growth at the cellular level [29].…”
Section: Furthermore It Has Been Shown That O-glcnac Modification Ofmentioning
confidence: 99%
“…It would be very challenging to distinguish the target specific effect from nontarget effect of such global approaches. Although it has been proposed that increased glucose uptake/glycolysis in cancer cells may lead to increased glucose flux through HBP and subsequently increased O-GlcNAc modification in a number of proteins [7,30]. However, to the best of my knowledge no attempt has been made to study the effect of inhibitors of glycolysis on HBP, O-GlcNAc level and O-GlcNAc protein modification in cancer cells.…”
Section: Furthermore It Has Been Shown That O-glcnac Modification Ofmentioning
confidence: 99%
See 1 more Smart Citation